Zmiany strategii zarządzania dystrybucją w sektorze ubezpieczeń w Polsce i krajach Unii Europejskiej w latach 2002–2008 - Kozak, Sylwester (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Integration with the European Union was a source of signifi cant changes in the Polish insurance sector. The period 2002–2008 was characterized with the increase of foreign capital investments and the increase of competition from domestic and foreign insurers. One of the most important consequences of that process was the broadening of the range of products and changing of the structure of distribution channels. The goal of the analysis is the examination of the directions and scale of changes in the structure of insurance products and the structure of distribution channels in the years 2002–2008. The research based on data form KNF. PIU i CEA indicate that insurance companies starting to offer more life insurance as an investment vehicle for households’ savings and reducing the share of communication insurance and increasing fi nancial and property insurance. Insurers transformed the distribution structure and signifi cantly increased the sales through the banking network and reduced the sales through their own facilities and insurance agents and brokers. Such trend brings closer the distribution structure of the Polish insurance sector to the structure of insurance sectors in Austria, Belgium, France and Italy, it means countries with the bankoriented fi nancial systems.